Dietary Components Associated with the Risk of Gastric Cancer in the Latin American Population: A Systematic Review and Meta-Analysis - Azalia Avila-Nava; Ana Ligia Gutiérrez-Solis; Oscar Daniel Pacheco-Can; Ian Yeshua Sagols-Tanoira; Roberto González-Marenco; Ana Gabriela Cabrera-Lizarraga; Jesús Abraham Castillo-Avila; Miguel Alberto Aguilar-Franco; Rodolfo Chim-Aké; Héctor Rubio-Zapata; Mariela Reyes-Sosa; Isabel Medina-Vera; et al. (Foods)
Gastric cancer is one of the most frequent cancer types in the Latin American population, and its development is related to multiple factors, including diet. The present systematic review and meta-analysis, based on PRISMA, aims to determine dietary components associated with gastric cancer in Latin America. The dietary components were divided into food and micro- and macronutrients. Meta-analyses were performed for the different groups of foods, and the effects were calculated using Odds Ratios. A total of 483 studies were identified; thirteen articles were included after removing duplicates and applying the inclusion and exclusion criteria. The meta-analysis for the different groups of food showed that daily consumption of vegetables (OR 0.54; 95% CI [0.41, 071]) and fruits (OR 0.57; 95% CI [0.45, 0.73]) were protective factors for gastric cancer; consumption of fresh meat and eggs (OR 1.47; 95% CI [1.12, 1.95]), and salted, canned, and pickled foods (OR 2.30; 95% CI [1.10, 4.80]) were risk factors for gastric cancer. Consuming carotenoids, plant sterols, total polyphenols, proteins, and polyunsaturated fats was a protective factor regarding micro- and macronutrients. Therefore, the consumption of nitrite and nitrate in meat products and capsaicin was considered a risk factor for gastric cancer.